2005
DOI: 10.4319/lo.2005.50.6.2008
|View full text |Cite
|
Sign up to set email alerts
|

The role of climate in shaping zooplankton communities of shallow lakes

Abstract: We analyzed data from 81 shallow European lakes, which were sampled with standardized methods, for combined effects of climatic, physical, and chemical features of food‐web interactions, with a specific focus on zooplankton biomass and community structure. multiple‐regression analysis showed that total phosphorus (TP) generally was the most important predictor of zooplankton biomass and community structure. Climate was the next most important predictor and acted mainly through its effect on pelagic zooplankton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
128
3
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(144 citation statements)
references
References 62 publications
12
128
3
1
Order By: Relevance
“…Shallow lakes are expected to be particularly influenced by climate warming (Baulch et al 2005;Carvalho and Kirika 2003;Gyllstrom et al 2005;Moss et al 2003). The fact that the global distribution of lakes is dominated by millions of small water bodies (Downing et al 2006) suggests that the response observed in this experiment to warming may be important to carbon cycling on a global scale.…”
Section: Discussionmentioning
confidence: 99%
“…Shallow lakes are expected to be particularly influenced by climate warming (Baulch et al 2005;Carvalho and Kirika 2003;Gyllstrom et al 2005;Moss et al 2003). The fact that the global distribution of lakes is dominated by millions of small water bodies (Downing et al 2006) suggests that the response observed in this experiment to warming may be important to carbon cycling on a global scale.…”
Section: Discussionmentioning
confidence: 99%
“…This is because submerged macrophytes in shallow lakes can form a dense vegetation that controls phytoplankton biomass through several mechanisms, including allelopathic interactions (Gross, 2003), nutrient limitation (Van Donk et al, 1993), shading and providing of a refuge for zooplankton that can control phytoplankton by grazing (Timms & Moss, 1984;Schriver et al, 1995;Burks et al, 2002). Recent studies indicate that zooplankton body size becomes smaller (Gillooly & Dodson, 2000) and that the zooplankton:phytoplankton biomass ratio declines from cold to warm lakes, likely due to enhanced fish predation (Lazzaro, 1997;Gyllström et al, 2005;Jeppesen et al, 2007a;Havens et al, 2009), and that the refuge capacity of submerged macrophyte for zooplankton is lower in warm lakes where fish are very abundant in the vegetation (Meerhoff et al, 2007a, b;Teixeira-de Mello et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature is one of the most important physical factors determining biological processes in aquatic environments (de Azevedo and Bonecker, 2003;Gyllström et al, 2008;Starmach et al, 1976;Vadadi-Fülöp et.al., 2009). The average water temperature in the oxbow lake isolated from the Vistula River was lower than in the lake connected with the river.…”
Section: Discussionmentioning
confidence: 99%